THE NEUROPROTECTIVE EFFECTS OF INHALED JUNIPERUS OXYCEDRUS L. SUBSP. OXYCEDRUS (CUPRESSACEAE) ESSENTIAL OIL ON SCOPOLAMINE-INDUCED ALZHEIMER'S TYPE DEMENTIA - OTHMAN, SAFEEN AHMED (Fırat Üniveristesi, 2018)
Bu çalışmada, Tıbbi bir bitki olan ve Türkiye' de doğal yayılışı bulunan Juniperus oxycedrus L. subsp. oxycedrus uçucu yağının skopolamin ile oluşturulan Alzheimer tipi demansa karşı sinir koruyucu etkileri araştırılmıştır. Juniperus oxycedrus subsp. oxycedrus özellikle Anadolu'da yıllardan beri geleneksel tıpta kullanılmaktadır. Juniperus oxycedrus uçucu yağı GC-MS ile analiz edilmiştir. Juniperus oxycedrus essential oil % 1and Juniperus oxycedrus essential oil %3 grupları 14 gün boyunca uçucu yağına maruz kalmışlardır.Uçucu yağda alfa-pinen (%42.9) major bileşen olarak bulunmuştur. Uçucu yağ solunumu Y-labirentinde spontan değişim yüzdesinde artışa, radial kol labirentinde işleyen hafıza hatalarında ve referans hafıza hatalarında düşüşe, yükseltilmiş artı labirentinde açık kola giriş sayılarında, sayılarında artışa kol zaman yüzdesi ve geçiş sayılarında artışa, zorunlu yüzme testinde yüzme süresinde artışa, hareketsizlik süresinde ise düşüşe yol açmıştır.

In this study, the neuroprotective effects of the essential oils from medicinal plant Juniperus oxycedrus L. subsp. oxycedrus distributed in Turkey on scopolamine induced Alzheimer's type dementia rat model were investigated. Alzheimer's disease is a neurodegenerative illness and increased more in the near future. Juniperus oxycedrus L. Subsp. oxycedrus has been used in traditional medicine for several years, especially in Anatolia. The essential oil of this plant was hydroditilled by Clevenger Apparatus and analyzed by GC-FID-MS. system. Different concentrations (1% and 3%) of the this plant essential oil inhaled to the animals for 14 continuous days. In the essential oil, ?-pinene (42.9 %) was found to be the the major component. Inhalation of this oil caused to increase spontaneous alternations % in Y-Maze tests and decreased working memory errors and reference memory errors in Radial Arm-Maze tests, increased the number of open-Arm Entries, increased open arm time percentage and number of Arm Crossings in Elevated Plus-Maze tests, increased swimming time and decreased immobility time in forced swimming test.
Skopolamin ile oluşturulan Alzheimer tipi demansa karşı Juniperus oxycedrus L. subsp. Oxycedrus uçucu ya?ı solunumunun sinir-koruyucu etkileri
Keywords: Biyoloji